THE IMPACT OF CREATING OAHU OCEAN GUIDE MAGAZINE AND WEBSITE FOR TOURISTS IN WATER SPORT - Banaser, Nouf Salem (Journal of Humanities & Social Sciences, 2019)
Tourists come from all over the world to visit Hawaii. When we mention Hawaii the first thing that brings to our minds the beaches, surfing, diving, and many different water sports. As well when we mention Water sports are associated with many hazards.Which led me to do this research after living in Hawaii for 3 years.I found out high proportion of injuries, drowning and deaths, because of:1- Lack of awareness of the dangers of water sports2- Lack of knowledge of the beaches suitable for the exercise of any kind of sport.3- Not take precautions of security and peace. I decided to pay back to Hawaii and for the beautiful years I spent there, by creating an educational magazine to educating tourists and those whose interested in water sports, specifically in Oahu, Hawaii. I named it “Oahu Ocean Guide"My research is focused on collecting information on safety tips and fishing systems as well as water activities such as swimming, windsurfing and scuba diving. Along with these activities come risks and how to prevent these dangers. In order to reach a wider audience, I have created a website that includes all ocean activities in addition to a guide explaining the risks of Hawaii's oceans.The magazine and the site together outline many risks as well as prevent them so that the tourist gets a safe holiday.
Keywords: Hawaii; water sports; surfing; risk